Indonesia’s Response to Covid-19 Outbreak: Raising Awareness through Community Engagement and Actionable Volunteer Contribution - Janette Maria Pinariya; Carelyn Josephine; Wulan Yulianti; Anita Yunia (Ikatan Sarjana Komunikasi Indonesia, 2021)
The world is in the grip of a health crisis due to the unforeseen consequences of the COVID-19 pandemic causing a substantial increase in distress associated with pain, depression, and loss. Indonesia is not handling the epidemic properly at this early stage due to a lack of planning and readiness on the part of the country. The government subsequently established the COVID-19 national task force, a COVID-19 assistance centre that reflects the government's readiness and urgency in dealing with the COVID-19 pandemic. At the national and regional levels, the task force reports directly to the president, organizes and encourages all connected agencies to respond to the COVID-19 crisis. The task force's other responsibility is to raise awareness about COVID-19 to the general public. The study aims to determine how Indonesia's COVID-19 task force volunteers can act as a communication aid for the public as a source of empowerment during the pandemic, as well as to examine risk communication and community engagement. This research uses a qualitative approach using the theory of social support. As a result, this study has identified new volunteering approaches for Indonesia's COVID-19 task force that could act as a support system as well as improvements on their approach on community engagement with the public.